Diversity and Abundance of Earthworms in Cocoa Plantations with Different Shade Trees - Niken Puspita sari; Rahayu Widyastuti; Soetanto Abdoellah (Indonesian Coffee and Cocoa Research Institute, 2021)
Earthworm is one of the important macro-fauna in cocoa plantation ecosystem that affects the structure and activity of soil microbes. Earthworms maintain nutrient cycle and affect the growth of plants. Cocoa is a plant that requires shade trees. The presence of shade trees is to increase soil fertility and enrich diversity offlora and fauna. The purpose of this study was to investigate the diversity and abundance of earthworms in cocoa farms with different shade trees, namely paranet, areca palm + leucaena, coconut + leucaena, oil palm + leucaena, and leucaena. The study was carried out in Kaliwining Experimental Station of Indonesian Coffee and Cocoa Research Institute, Jember. Earthworms were picked manually to a depth of 30 cm by purposive sampling method from July to October 2020. The cocoa plants used were mature plants with a spacing of 3 m x 3 m. Based on Shannon and Wiener formula, the results showed that earthworm diversity was low in all treatments. Earthworms until family level were identified. Earthworm families of Glososscolicidae and Megascolocidae were found in this study. The highest abundance of earthworms was found in areca palm + leucaena. Soil organic C and N content and sand fraction were positively correlated with earthworm abundance, while silt fraction and soil density were negatively correlated with earthworm abundance. As micro-climate factor, light intensity was positively correlated with earthworm abundance, while air temperature was negatively correlated with earthworm abundance.